On the influence of the inlet slug length distribution- a slug flow simulator - T. Sotto Mayor (2004)
A slug flow simulator was developed considering: (i) an overtaking mechanism based on air-water co-current continuous experimental data [1]; (ii) expansion of the gas phase and its consequences in bubble length and velocity and (iii) several types of slug length and gas flow rate distributions, at column inlet. The simulator allows the monitoring of various flow characteristics, namely (i) the evolution of the distributions of several variables along the column; (ii) the definition of column zones, with different coalescence and (iii) the evaluation of the flow stability height (flow developing length), for certain flow conditions. The simulator was used to study the influence of the inlet slug length distribution over the stabilized slug flow pattern. Four similar simulations were prepared with inlet slug lengths normally distributed around averages of 0.075, 0.1, 0.15 and 0.2 m, and equal initial number of bubbles, inlet gas flow rate, and liquid flow rate. The output results showed to be independent of the inlet distributions, indicating that the bubble overtaking mechanism has dominant influence over the overall slug flow pattern development.